Gaps in Examination Records Management Procedures: The Reasons for Missing Marks Syndrome in Universities in Kenya - Kiprono, Samuel Serem; Gichuhi, Zipporah W. (International Journal of Professional Practice, 2021)
Universities are institutions of higher education which confer undergraduate and postgraduate degrees in a variety of subjects. There is need for greater care in the management of examination records at every stage of the university student’s life cycle so as to avoid the pain of students failing to graduate on time. This study was conceived with the purpose of establishing if examination records management procedures could be the cause of missing examination marks in universities in Meru and Nyeri counties in Kenya. The objective in this paper is to demonstrate the relationship between missing marks and examination records management procedures in universities. Descriptive survey research design was used in the study. Target population of 482 full time lecturers and school examination coordinators with sample size of 214 respondents, and whose response rate was 128(60%) was used. Structured questionnaires were used to collect data. Data was analyzed using descriptive statistics. The findings revealed that the selected universities had documented examination records management procedures that were updated after every five years; unfortunately, the enforcement of the procedure was lacking. The study concludes that the main cause of missing marks in the universities was lack of central enforcement of examination procedures. The study recommends the training of all lecturers and examination coordinators on basic records management to ensure adherence to examination procedures to check cases of missing marks and scripts.